Tendon-derived stem cells from the long head of the biceps tendon: Inflammation does not affect the regenerative potential. Issue 9 (September 2019) - Schmalzl, Jonas; Plumhoff, Piet; Gilbert, Fabian; Gohlke, Frank; Konrads, Christian; Brunner, Ulrich; Jakob, Franz; Ebert, Regina; Steinert, Andre F.
Abstract : Objectives: The long head of the biceps (LHB) is often resected in shoulder surgery and could therefore serve as a cell source for tissue engineering approaches in the shoulder. However, whether it represents a suitable cell source for regenerative approaches, both in the inflamed and non-inflamed states, remains unclear. In the present study, inflamed and native human LHBs were comparatively characterized for features of regeneration. Methods: In total, 22 resected LHB tendons were classified into inflamed samples (n = 11) and non-inflamed samples (n = 11). Proliferation potential and specific marker gene expression of primary LHB-derived cell cultures were analyzed. Multipotentiality, including osteogenic, adipogenic, chondrogenic, and tenogenic differentiation potential of both groups were compared under respective lineage-specific culture conditions. Results: Inflammation does not seem to affect the proliferation rate of the isolated tendon-derived stem cells (TDSCs) and the tenogenic marker gene expression. Cells from both groups showed an equivalent osteogenic, adipogenic, chondrogenic and tenogenic differentiation potential in histology and real-time polymerase chain reaction (RT-PCR) analysis. Conclusion: These results suggest that the LHB tendon might be a suitable cell source for regenerative approaches, both in inflamed and non-inflamed states. The LHB with and without tendinitis has been characterized as a novel source of TDSCs, which might facilitate treatment of degeneration and induction of regeneration in shoulder surgery. Cite this article : J. Schmalzl, P. Plumhoff, F. Gilbert, F. Gohlke, C. Konrads, U. Brunner, F. Jakob, R. Ebert, A. F. Steinert. Tendon-derived stem cells from the long head of the biceps tendon: Inflammation does not affect the regenerative potential. Bone Joint Res 2019;8:414–424. DOI: 10.1302/2046-3758.89.BJR-2018-0214.R2.